Perceived Marketing System Effectiveness by Pineapple Growers in Tripura - Roy, Priyanka; Ghosh, Souvik (Indian Journal of Extension Education, 2022)
Pineapple, an important cash crop of Tripura providing the major source of farm livelihood, has been facing marketing challenges. Present study was conducted during January-June 2020 to assess farmers’ perceptions towards marketing system effectiveness of pineapple that included a random sample of 80 farmers. Marketing system effectiveness was measured on different aspects of pineapple marketing based on farmers’ perceptions on 5-point continuum. Higher mean perception scores (>4.0) were obtained for two aspects viz., grading & quality checking, and direct selling of produce. Contrastingly, lower perception scores (
Keywords: Pineapple; Farmers’ perception; Marketing; Marketing system effectiveness; Attributes